Venture Capital Investment Strategy and Portfolio Failure Rate: A Longitudinal Study - Dimov, Dimo; De Clercq, Dirk (Entrepreneurship Theory and Practice, 2006)
Given the importance and prevalence of new venture failure, having a better understanding of the factors that affect its occurrence is a paramount research objective. In view of the increased focus on venture capital firms (VCFs) as important stakeholders for entrepreneurial ventures, in this study we examined the relationship between VCFs’ investment strategies and their portfolio failure rates. We examined two aspects of a VCF's investment strategy: (1) the extent to which the VCF develops specialized expertise and (2) the extent to which the VCF undertakes investments in cooperation with other investors through syndication. We tested our hypotheses on longitudinal data of the realized strategies of 200 U.S.–based VCFs over a 12–year period. We found that a VCF's specialized development stage expertise had a negative effect on the proportion of defaults in the VCF's portfolio. We also found that the level of syndication positively—rather than negatively—affected the proportion of defaults. We discuss our findings from both theoretical and practical points of view.